Exploring Flashcard as the Media in Teaching Vocabulary to EFL Young Learners - Eka Rahma Widya; Agis Andriani; Fera Sulastri (Journal of Applied Linguistics (ALTICS), 2021)
This study aims to find out how the teacher's experience in teaching flashcards in the Young Student Class. The participant is an English teacher, in elementary school. Data were collected through interviews. Data were analysed using thematic analysis (Braun & Clarke, 2006). The data shows that there is experience when teaching using flashcards, namely the impact of using flashcards in teaching and challenges or difficulties when teaching vocabulary using flashcards. The findings show that teaching vocabulary to young learners using flashcards helps teachers. Teaching vocabulary using flashcards is the right medium for young learners. It makes the teacher feel various feelings while doing it, and the participants feel happy and helped. This happened because at first young students were happy but also confused but in fact they became enjoy, happy, able to follow the lesson well, conducive, achieve learning goals and become interested in learning to use flashcards after getting used to it. So, in this study flashcards can help teachers to teach vocabulary to young learners. This study contributes that flashcards can help teachers when teaching, it can help teachers when teaching new vocabulary to students.